Haji Bektash Vali’s Life and the History of Bektashism - Orujov, Emin (Scholarya Demo Journal of Ruby, 2022)
This study explores the life of Haji Bektash Vali as well as the history of Bektashism. First, the legend of Haji Bektash Vali’s life and work is studied, including the years of birth and death, his arrival in Anatolia, various assumptions about whether he was married or not, whether he was Turkish or Arab, and information about his works. Then, the stages of formation of Bektashism and sectarianism are studied. Examining the history of Sufism, we can see the exceptional role of the Sufis in the spread of Islam since the 10th century. Sectarianism develops in Sufism beginning in the 12th century. Hurufism, Khalwatism, Yasavism, Nagshbandism, and other Sufi sects have spread since then. Haji Bektash Vali began spreading the central idea of Bektashism in the Anatolian region in the 12th century, and it later spread to Egypt, Eastern Europe, and the Balkans. The idea and philosophy of Bektashism were spread through disciples after Haji Bektash Vali. Bektashism was also instrumental in the establishment of the Ottoman Empire’s Guild of Janissaries.